An atlas of wing photographs and a key to species of the genus Culicoides Latreille from Mexico (Diptera: Ceratopogonidae), including new records, new synonymy, two new species and new status of Culicoides neghmei Vargas and C. propinquus Macfie - Huerta, Herón; Spinelli, Gustavo R.; Jr, William L. Grogan (Zootaxa, 2025)
An atlas of wing photographs and a key to 91 species of biting midges in the genus Culicoides from Mexico. Culicoides (Diphaomyia) evansi Wirth & Blanton from Morelos and C. (Drymodesmyia) pilosus Wirth & Blanton from Hidalgo are recorded from Mexico. Two new species from Chiapas are described and illustrated, Culicoides ostotlae sp. nov. in the Daedalus group and Culicoides tzotzil sp. nov. in the subgenus Diphaomyia. We proposed a new status for Culicoides neghmei Vargas in the Limai group, which is closely related to C. luglani Jones & Wirth, and C. propinquus Macfie to be included in the subgenus Drymodesmyia. Culicoides wirthomyia Vargas is now a junior synonym of C. jamaicensis Edwards.